Senegal : Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report, 2020)
This paper presents Senegal's Request for Disbursement Under the Rapid Credit Facility (RCF) and Purchase Under the Rapid Financing Instrument (RFI). The sharp global economic downturn and domestic containment measures have led to a substantial reduction in economic activity, with sectors such as tourism, transport, construction, and retail particularly hard-hit, and the pandemic in Europe is also translating into lower remittances. As a result, the short-term economic outlook has deteriorated significantly, with large uncertainties surrounding the duration and spread of the pandemic. The IMF's emergency financing under the RCF and the RFI is expected to provide much-needed liquidity to support the authorities' response to the crisis and could catalyze further assistance from the international community, preferably in the form of grants. Additional concessional donor support will be critical to close the remaining financing gap, ease the adjustment burden, and preserve Senegal's impressive economic achievements. Ensuring that disbursed funds are used in a well-targeted, cost-effective and transparent manner remains imperative.